Biologicals in atopic disease in pregnancy: An EAACI position paper. Issue 1 (7th January 2021) - Pfaller, Birgit; José Yepes‐Nuñez, Juan; Agache, Ioana; Akdis, Cezmi A.; Alsalamah, Mohammad; Bavbek, Sevim; Bossios, Apostolos; Boyman, Onur; Chaker, Adam; Chan, Susan; Chatzipetrou, Alexia; du Toit, George; et al.
Abstract: Biologicals have transformed the management of severe disease phenotypes in asthma, atopic dermatitis, and chronic spontaneous urticaria. As a result, the number of approved biologicals for the treatment of atopic diseases is continuously increasing. Although atopic diseases are among the most common diseases in the reproductive age, investigations, and information on half‐life, pharmacokinetics defining the neonatal Fc receptors (FcRn) and most important safety of biologicals in pregnancy are lacking. Given the complex sequence of immunological events that regulate conception, fetal development, and the intrauterine and postnatal maturation of the immune system, this information is of utmost importance. We conducted a systematic review on biologicals in pregnancy for indications of atopic diseases. Evidence in this field is scarce and mainly reserved to reports on the usage of omalizumab. This lack of evidence demands the establishment of a multidisciplinary approach for the management of pregnant women who receive biologicals and multicenter registries for long‐term follow‐up, drug trial designs suitable for women in the reproductive age, and better experimental models that represent the human situation. Due to the very long half‐life of biologicals, preconception counseling and healthcare provider education are crucial to offer the best care for mother and fetus. This position paper integrates available data on safety of biologicals during pregnancy in atopic diseases via a systematic review with a detailed review on immunological considerations how inhibition of different pathways may impact pregnancy.